Measurement of isotope fractionation associated with crystal nucleation: Implications for biocrystallization studies - Chuan Liu; Thomas L. Goût; Yandi Hu; Weiqiang Li; Shichao An; Zehao Zhou; Song Cai; Huazhang Zhao; Jinren Ni; James J. De Yoreo; Donald J. DePaolo (Proceedings of the National Academy of Sciences, 2026)
Isotopic fractionation is a unique indicator of the mechanisms of mineral precipitation from aqueous solutions, but existing theory does not account for nucleation effects or nonclassical growth mechanisms. Here, using barite (BaSO 4 ) as a model crystal, we provide an experimental measurement of isotope fractionation associated with nucleation. We isolated nucleation effects by precipitating crystals on an organic film, where cation enrichment creates a highly supersaturated microenvironment so nucleation dominates over crystal growth. In a single batch experiment, we retrieved nanocrystals (~1.5 nm) from the organic substrate and large microcrystals in bulk solution where growth dominates. The 138 Ba/ 134 Ba isotopic fractionation of −0.6 to −0.8‰ for the microcrystals match those expected for classical ion-by-ion growth from a moderately supersaturated solution, whereas the fractionation for the nucleation-dominated nanocrystals is about −0.1‰, falling within the reported equilibrium fractionation range between barite and aqueous Ba 2+ . These results demonstrate that cation isotopic fractionation in sparingly soluble salts like barite and calcite is not a single-valued function of saturation indices (SI) and precipitation rate as predicted with current theory, with the fractionation factor (∆ 138/134 Ba barite-soln = δ 138/134 Ba barite − δ 138/134 Ba solution ) increasing in magnitude with increasing SI. Instead, the shifting precipitation mechanism(s) at high SI cause the fractionation factor to return to near-equilibrium values. This finding may be critical for understanding isotopic fractionation in localized extreme environments in nature, including for Ba isotopes during biomineralization.